Sanacija kamnoloma Podsmreka po načelu zaprtega ekološkotehnološkega kroga pridobivanja rudnin - perspektiva za prihodnje - Žibret, Gorazd (Geologija, 2004)
The main idea is how we could use the scrapped construction materials for the recultivation of abandoned extraction sites in the means of closed cycle from extraction of the non metallic mineral resourced, consumption and deposition at the end. In the article the Slovenian law concerning this area and the casestudy of Podsmreka quarry is described. The process takes the opposite direction from extraction, which means that the company does not need a lot ofadditional equipment. This is a good option for the environment, society andfor the companies after finishing the exploitation.
Keywords: gradbeni odpadki; kamnolomi; mineralne surovine; odlagališča; Podsmreka; ravnanje z odpadki; sanacija; Slovenia; Slovenija